Evaluating the performance of Moroccan social incubators: an SFA analysis of youth platforms under the national initiative for human development - El Maaqili, Younes; Tlemcani Mhandez, Mariam; Ouchen, Abdessamad (Business, Management and Economics Engineering, 2025)
Purpose – This study focuses on the evaluation of youth platforms as an important  social incubator of the National Initiative for Human Development (NIHD) in Morocco, particularly to promote social entrepreneurship and support very small enterprises (VSE). Numerous social incubators have been created to support social entrepreneurship and foster innovative and effective socio-economic relations. However, their impact remains limited, raising  questions about their performance.Research methodology – Based on a sample of 40 NIHD youth platforms, the stochastic frontier analysis (SFA) method was applied to measure their technical efficiency (TE), and then the  determinants of the TE obtained were analysed by a regression using the Tobit model. Findings – The results indicate that management costs (MC), the number of accompanied  project holders (APH) and income improvement actions in social and solidarity economy (II- ASSE) have a significant impact on the creation and development of VSE or cooperatives. In  addition, the experience of the platform manager has a positive influence on TE, while age  has no significant effect.Research limitations – The conclusions of the study may not be entirely applicable to the  current situation of NIHD youth platforms in Morocco, because they are based on data available at a time conditioned by an exceptional context (e.g., post-covid; government austerity  policy, etc.). Practical implications – This study provides public policymakers and platform managers with  actionable insights into optimizing resource use and improving platform operations. Policy-makers can use the findings to allocate funding more effectively, prioritize support services  like income improvement actions, and identify platforms that serve as benchmarks for best  practices. Additionally, the study highlights the importance of experienced platform managers,  guiding recruitment and training policies to improve platform outcomes.Originality/Value – The study paves the way for future research aimed at exploring in more  depth the underlying mechanisms of the efficiency of NIHD youth platforms.